An Inclusive OER Pedagogy in Teaching Music Technology in Higher Ed - Jiayue Cecilia Wu (Journal of the Association for Technology in Music Instruction, 2025)
As a Colorado State's Open Educational Resources (OER) funding award recipient, I will present the application of an OER approach in teaching music technology, utilizing free and/or open-source materials, tools, and textbooks/publications. Drawing on two courses I have successfully taught using this methodology, I will highlight practical implementation strategies and their impact. Furthermore, I will introduce national OER funding resources and guide the application process. I will enable music educators to adopt this approach in their teaching practices, enhance their scholarly publications, and secure funding support for academic initiatives.